Weight Perception among Non-pregnant Urban Malaysian Women: Is It Reliable? - Fariza Fadzil,; Khadijah Shamsuddin,; Sharifa Ezat Wan Puteh,; Shuhaila Ahmad,; Noor Shaheeran Abdul Hayi,; Azah Abdul Samad,; Ruhaini Ismail,; Nor Izzah Ahmad Shauki, (Universiti Kebangsaan Malaysia, 2015)
Introduction In maternal healthcare, pre-pregnancy weight is used to predict pregnancy outcomes. Since no recorded data on pre-pregnancy weight, perceived weight is used alternatively. This study examines the relationship between perceived and actual weight among non-pregnant urban Malaysian women of childbearing age and identifies differences in perceived and actual weight by selected socio-demographic characteristics.